Congenital Adrenal Hyperplasia with Concomitant Mullerian Agenesis: A Rare Occurrence in 46 XX Disorders of Sexual Development - Wahyuni, Zulfia; H, Yuad; Y, Margareta Sari (Syntax Corporation, 2023)
The most common cause of 46 XX DSD is due to congenital adrenal hyperplasia with varying degrees of virilization. Females with CAH do not produce an anti-mullerian hormone (AMH), therefore the internal genitalia, which are Mullerian derivatives, develop normally. We report a unique case of CAH with aplasia of the uterus and upper vagina. The clinical, laboratory, and imaging findings of the patient are presented with a review of the literature. We report an ongoing case of a 20-year-old patient with ambiguous genitalia and primary amenorrhea. On physical examination, we found that she had an underdeveloped breast and clitoral virilization with separate urethral and vaginal openings. We performed a G-banded chromosome analysis, with 46 XX results. Laboratory test showed her 17-hydroxyprogesterone level was immensely elevated, while her FSH, LH, and estradiol level was below normal. Ultrasound imaging revealed the absence of uterus and cervix. Nevertheless, we found a diminutive uterine remnant during diagnostic laparoscopy with normal ovaries and fallopian tubes. On vaginoscopy examination, we found her vagina to be 5 cm long with blind end. In the presence of primary amenorrhea in patients with CAH, it is important to investigate for possible associated mullerian anomalies.